2021
DOI: 10.1021/acscentsci.1c00866
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Curcumin Nanozyme-Mediated Reactive Oxygen Species Scavenging and Anti-Inflammation for Acute Lung Injury

Abstract: Pneumonia, such as acute lung injury (ALI), has been a type of lethal disease that is generally caused by uncontrolled inflammatory response and excessive generation of reactive oxygen species (ROS). Herein, we report Fe-curcumin-based nanoparticles (Fe-Cur NPs) with nanozyme functionalities in guiding the intracellular ROS scavenging and meanwhile exhibiting anti-inflammation efficacy for curing ALI. The nanoparticles are noncytotoxic when directing these biological activities. Mechanism studies for the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(83 citation statements)
references
References 46 publications
1
78
0
Order By: Relevance
“…All of the mice were allocated into six groups at random according to their body weight. Intratracheal injection (i.t) was used to establish an ALI model as our previous study (21). Briefly, mice were injected with 0.4% sodium pentobarbital (i.p.)…”
Section: Lps-induced Acute Lung Injury Of Micementioning
confidence: 99%
“…All of the mice were allocated into six groups at random according to their body weight. Intratracheal injection (i.t) was used to establish an ALI model as our previous study (21). Briefly, mice were injected with 0.4% sodium pentobarbital (i.p.)…”
Section: Lps-induced Acute Lung Injury Of Micementioning
confidence: 99%
“… 18 Nanoparticles have been designed to penetrate the mucosal barrier for antigen delivery or for therapeutic application. 19 , 20 In addition, nanoparticle combinations with adjuvants have been utilized to improve protein immunogenicity. 21 The 24-unit Helicobacter pylori ( H. pylori ) ferritin spontaneously assembles nanoparticles harboring eight three-fold symmetric axes, 22 which has shown excellent potential in enhancing immune responses for trimeric antigens like influenza hemagglutinin 23 or EBV glycoprotein 350.…”
Section: Introductionmentioning
confidence: 99%
“…There is more oxidative stress (Jiao et al, 2022), or damage from things like pollution and sunlight, in their tears. Recently, it was suggested that the increased ROS activated the inflammasome NLRP3, which caused this immune-inflammatory response (Yuan et al, 2022;Wan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%